2014
DOI: 10.2220/biomedres.35.37
|View full text |Cite
|
Sign up to set email alerts
|

Three types of macrophagic cells in the mesentery of mice with special referenceto LYVE-1-immunoreactive cells

Abstract: Immunohistochemistry using whole mount preparations of the murine mesentery revealed two types of LYVE-1-immunoreactive cells with dendritic morphology other than F4/80 + typical macrophages. The two types of LYVE-1 + cells were regularly distributed with constant intervals throughout the mesentery and appeared to possess their own territory. Both types of LYVE-1 + cells were weakly or moderately immunopositive for F4/80 antibody, a marker of macrophages, while F4/80 + round macrophages were absolutely free fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
3
15
1
Order By: Relevance
“…Noteworthy, the expression of hyaluronidases there was restricted to macrophages but not reticular cells. Ultrastructually, LYVE-1 is always localized in the plasma membrane but not in the cytoplasm and cell organelle, in contrast to its cytoplasmic localization in macrophagic cells, such as intracellular vesicles and vacuoles (21,41). The dual membrane localization of LYVE-1 in the vascular endothelial cells is in agreement with early observations concerning LYVE-1 in the endothelium of lymphatics (29), suggesting transport via the cells (transcytosis) without intracellular degradation.…”
Section: Topographical and Functional Relationship Between Lyve-1-expsupporting
confidence: 87%
See 2 more Smart Citations
“…Noteworthy, the expression of hyaluronidases there was restricted to macrophages but not reticular cells. Ultrastructually, LYVE-1 is always localized in the plasma membrane but not in the cytoplasm and cell organelle, in contrast to its cytoplasmic localization in macrophagic cells, such as intracellular vesicles and vacuoles (21,41). The dual membrane localization of LYVE-1 in the vascular endothelial cells is in agreement with early observations concerning LYVE-1 in the endothelium of lymphatics (29), suggesting transport via the cells (transcytosis) without intracellular degradation.…”
Section: Topographical and Functional Relationship Between Lyve-1-expsupporting
confidence: 87%
“…The dual membrane localization of LYVE-1 in the vascular endothelial cells is in agreement with early observations concerning LYVE-1 in the endothelium of lymphatics (29), suggesting transport via the cells (transcytosis) without intracellular degradation. Our immunohistochemical data showed that the LYVE-1-immunoreactive cells were topographically associated with a dense distribution of macrophages in each tissue: Kupffer cells in the hepatic sinusoids, LPS (41). In contrast, the present study showed that LPS stimulation conversely increased the expression of LYVE-1 in the endothelial cells of the liver and lung, as demonstrated by quantitative RT-PCR and immunostaining.…”
Section: Topographical and Functional Relationship Between Lyve-1-expcontrasting
confidence: 60%
See 1 more Smart Citation
“…If and how these contribute to the immunological situation in the eye is unknown, but could be related to the high content of vitreous hyaluronan, as speculated earlier in a nonocular mouse model. 63 Because podoplanin expression was also found in a subset of F4/80positive macrophages, 64 the here detected single podoplaninpositive cells therefore might also represent macrophages, however, due to antibody incompatibility, were unable to test for this. Regarding luminal structures with vessel-like character positive for podoplanin, these were very few and the immunoreactive signal was very weak compared with other signals.…”
Section: Discussionmentioning
confidence: 79%
“…Although 38M and 64R reacted with lymphatic vessels in mouse tissues (Figure ) but not with blood vessels (Figure ), several studies have reported LYVE‐1 in CD11b‐ or F4/80‐positive macrophages . 38M and 64R, however, did not react with thioglycollate‐induced macrophages (data not shown), indicating that the epitopes recognized by 38M and 64R are preferentially expressed on the endothelia of lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%